2018
DOI: 10.3389/fcimb.2018.00307
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Signatures Can Aid Diagnosis of Sexually Transmitted Infection-Induced Endometritis in Women

Abstract: Sexually transmitted infection (STI) of the upper reproductive tract can result in inflammation and infertility. A biomarker of STI-induced upper tract inflammation would be significant as many women are asymptomatic and delayed treatment increases risk of sequelae. Blood mRNA from 111 women from three cohorts was profiled using microarray. Unsupervised analysis revealed a transcriptional profile that distinguished 9 cases of STI-induced endometritis from 18 with cervical STI or uninfected controls. Using a hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The cytokine ratios determined to be associated with chlamydial susceptibility can be prospectively examined in an independent cohort to test their ability to predict endometrial infection. Incorporation of host gene expression signatures [19,49], and other potential factors associated with chlamydial susceptibility such as the vaginal microbiome [50] could improve the predictive accuracy and may also allow for prediction of risk for repeat infection. In addition, our determination of protective responses that are detectable at the cervical mucosa during natural infection have provided important information for vaccine development, regarding specific chemokines and cytokines that might be incorporated as adjuvants to drive Th1 responses necessary for protection against this highly prevalent intracellular pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine ratios determined to be associated with chlamydial susceptibility can be prospectively examined in an independent cohort to test their ability to predict endometrial infection. Incorporation of host gene expression signatures [19,49], and other potential factors associated with chlamydial susceptibility such as the vaginal microbiome [50] could improve the predictive accuracy and may also allow for prediction of risk for repeat infection. In addition, our determination of protective responses that are detectable at the cervical mucosa during natural infection have provided important information for vaccine development, regarding specific chemokines and cytokines that might be incorporated as adjuvants to drive Th1 responses necessary for protection against this highly prevalent intracellular pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional profiling of trachoma conjunctival samples showed transcriptional networks connected to the innate immune response (42,43). Biomarker studies of women with chlamydial endometritis found increased expression levels of myeloid mediators of inflammation (44). We found that Pgp3-mediated persistent infection caused chronic macrophage immunopathology in the mouse model.…”
Section: Discussionmentioning
confidence: 72%
“…The expression of LYSMD2 was also downregulated in IF birds compared to both AL and CR. Although the actual function of the gene is yet unknown, it appears to be related to myeloid cell-mediated inflammation in humans (37) and has been found to be overexpressed in mice with fatty liver-induced hepatocellular carcinomas (38). In dogs undergoing surgery for congenital portosystemic shunts, low hepatic expression of NFE2L2 during surgery is a predictor of poor recovery (39).…”
Section: Discussionmentioning
confidence: 99%